Hydromulches suppress weeds and maintain fruit production in organically managed strawberry systems - Ahmad, Waqas; DeVetter, Lisa W.; McFadden, Dakota; Maupin, Brian; Bajwa, Dilpreet S.; Durado, Andrew; Weyers, Sharon; Galinato, Suzette P.; Weiss, Ben; Gramig, Greta (Frontiers in Agronomy, 2024)
Polyethylene (PE) mulches are widely used in strawberry (Fragaria × ananassa Duch) production for weed suppression and crop growth optimization. However, PE mulches are not biodegradable and contribute to plastic pollution. Our objective was to develop and test biodegradable liquid-applied ‘hydromulches’ (HMs) as a sustainable alternative to PE mulch. HM weed suppression efficacy, strawberry plant growth, and yield were evaluated. HM formulations consisted of shredded newsprint paper (NP), water, and a tackifier, either guar gum (GG) or psyllium husk (PH) added at 2 or 6%. Experiments were conducted at two environmentally distinct locations: northwest Washington (WA) and eastern North Dakota (ND). Five HM formulations were compared to black PE mulch within a randomized complete block design with four replications. PE mulch suppressed weeds completely at peak weed emergence and peak weed vegetative growth at both locations. Formulations of HM containing GG provided superior weed suppression compared to other HM formulations at peak weed emergence (4-6 and 18-22 plants m-2, respectively). At peak vegetative growth, HM formulations containing GG had the lowest weed density compared to other HMs in ND (1 vs. 9-12 plants m-2), whereas these differences were not observed in WA. Total weed biomass did not differ among HMs across both locations. GG HM formulations deteriorated similarly to PE mulch (3-5% vs. 2%, respectively) in ND, whereas other HMs deteriorated more substantially. In WA, all HMs deteriorated more than PE mulch (6-12% vs. 1%, respectively). Fruit yield did not differ among treatments in weedy and weed-free subplots (194-254 g plant-1) in WA. In ND, yield was greater in all HM treatments compared to PE mulch in both weedy and weed-free subplots. Across both locations, strawberry canopy cover was greater in PE mulch (56.1% canopy cover) compared to 2%GG and NP (42.4 and 39.8% canopy cover). Strawberry plant biomass was similar among mulch treatments. However, strawberry leaf and crown biomass were slightly lower in 2%PH compared to other mulch treatments. Results demonstrate HMs with GG tackifier are a promising alternative to PE mulch in organic strawberry systems based on ability to suppress weeds, enhance strawberry growth, and maintain yield.